Monitoring the Evolution of Pseudomonas aeruginosa Resistance against Routine Antibacterial Agents - Khacha, N; Bendjeddou, A; Abbaz, T; Chettebi, H (My University, 2017)
ABSTRACT Bacterial resistance to antibacterial is a major public health problem. To contribute to the monitoring of multidrug resistance of Pseudomonas aeruginosa, we have tested 356 strains. These were isolated from pathological products of outpatient or inpatient. These strains were identified by the highlighted specific pigments and gallery API 20NE then submitted to several sensitivity tests against antibacterial agents. The latter was evaluated by the diffusion method on agar medium. For chlorinated water which is the most widely used disinfectant worldwide, we sought the lethal concentrations by liquid-based diffusion method. The results demonstrated that among the amino glycoside only amikacin showed significant efficacy. Among beta-lactam, the imipenem and piperacillin are the most effective relative to other antibiotics tested. Among the antiseptics tested only hydrogen peroxide at 10 volumes demonstrated efficacy compared with iodine alcohol at 10% and surgical alcohol at 70°. Strains tested showed a tolerance at concentrations at least most important chlorinated water at 13 °. The latter has a static effect only up to 2%.